(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Domestic and family violence has been present since ancient times in human history, and in Brazilian history, since the period of discovery, it was common to treat women differently. This situation only began to be reconsidered from another perspective in the mid-twentieth century, when women started gaining rights previously exclusive to men and greater political protagonism. In the justice system, until a few years ago, victims were treated with indifference, a situation that began to change with the enactment of Law No. 11,340/2006, which granted greater protection, although further progress in protection and policy development is still needed. Objective: To present relevant information regarding the treatment of victims and to understand how the Brazilian justice system acts in the prevention and protection of victims of domestic violence. Methods: This is a theoretical and reflective study based on the author’s experience in the Brazilian justice system, aiming to understand the needs of victims and the best application of the law. Results: The analysis showed that, despite the advances achieved in recent years, further improvements are needed to make protection and prevention truly effective. Conclusion: It is concluded that Brazil has been striving to comply with international treaties and internal legislation; however, greater effectiveness in public policies is essential, especially in inland regions, to ensure adequate protection for victims.